HIV pre-exposure prophylaxis for women - Anandi N. Sheth; Charlotte P. Rolle; Monica Gandhi (Elsevier, 2016)
Women and girls comprise nearly half of HIV-infected individuals globally and 20% of new infections in the United States, indicating an urgent need to optimise HIV prevention options in this population. HIV pre-exposure prophylaxis (PrEP) - where antiretrovirals are administered to HIV-non-infected individuals at risk of HIV acquisition - is a promising, female-controlled HIV prevention strategy but has so far been underutilised in women. Clinical trial data demonstrate efficacy of daily oral tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) for reduction of HIV acquisition among women when used consistently. Limited HIV risk perception and suboptimal PrEP awareness among women and healthcare personnel are among the challenges with PrEP delivery for women. Future research into the development of new drugs and delivery systems, and integrating PrEP delivery with reproductive healthcare services, provide opportunities to optimise this prevention strategy for women.